(untitled) (Research, Society and Development, 2021)
This work aims to analyse some concepts about public access policies education according to the proposed articles initially in the declaration of human rights and nowadays, after 70 years of DDH approval. Differentiate the concepts of humans rights education between the humans rights education in the light of studies by some authors. The university is a privileged place of formation and information to the students and future professionals with clear predictions in public policies to the education in human rights in higher education. At least, check how the programmatic actions are doing to the education in human rights in the HEI (Higher Education Institutions), whose scenario is conducive to the discussion on these policies, reflected and made positive according to PNDH (Plano Nacional de Direitos Humanos - National Human Rights Plan ), federal government program created from the art. 84, item IV, from constitution, by decree nr. 1904 from may 13, 1996, containing diagnosis of the situation of these rights in the country and measure for its defense and promotion; and according to PNEDH ( National Human Rights Education Plan - Plano Nacional de Educação em Direitos Humanos), the result of the state´s commitment to the realization of human rights and a historic construction of organized civil society.